THE CONCEPT OF THE RULE OF LAW IN THE INDONESIAN CONSTITUTION - Petra Ginting, Brianta; Suganda, Atma; Suasungnern, Sineerat (Penerbit Lafadz Jaya, 2024)
This research aims to analyse the concept of the rule of law in the 1945 Constitution of the Republic of Indonesia (UUD 1945) and evaluate the extent to which the principle of the rule of law is implemented in Indonesia's constitutional structure. Using a normative juridical approach and a positivistic paradigm, this research finds that the implementation of the principle of the rule of law in Indonesia still faces significant challenges, including inharmonious regulations, corruption, and limited independence of the judiciary. This research provides recommendations for improvements to the legal system and government institutions to reflect the principle of the rule of law that is more consistent with constitutional values, which is expected to strengthen fair and transparent legal governance in Indonesia.